PENENTUAN NILAI PARAMETER KINETIKA LUMPUR AKTIF UNTUK PENGOLAHAN AIR LINDI SAMPAH (LEACHATE) - Muhammad Romli, Suprihatin dan Dinna Sulinda (Jurnal Teknologi Industri Pertanian, 2004)
ABSTRACTLeachate is one of the inevitable consequences of the practice of solid waste disposal in open dumping that can cause environmental problem, especially water pollution. The biological methods have been proved as an efficient alternative for the treatment. Designing the best operational system for leachate treatment would require the determination of the biological kinetics that are valid only for a certain practiced process. Two types of open dumping leachates, which were taken from drought and rainy season, were used to determine the kinetics, Yg, Ks and b. The acclimated activated sludge was used in three batch reactors with different initial MLVSS concentration (1700, 500 and 400 g/l for 1st, 2nd, and 3rd reactors). The parameters observed on this research were COD (Chemical Oxygen Demand), MLSS (Mixed Liquor Suspended Solids) and MLVSS (Mixed Liquor Volatile Suspended Solids). The research shown that  value ranges from 0.058 to 0.372 (dˉ1), Yg value ranges from 0.6166 to 0.9114 (mg MLVSS/mg COD), Ks value ranges from 353.4 to 3362.1 (mg/l), and b value ranges from 0.1248 to 0.132 (dˉ1), for the dissolved oxygen of 2.7-4.6 mg/l and pH value around 7-9. The parameters of bioreactor design were calculated based on the 3rd reactor kinetic values for the influent flow rate (Q) of 20 m3/d, the mean cell-residence time (c) of 10 days and the MLVSS concentration of 3200 mg/l, with COD and BOD5 of 10 000 mg/l and 3800 mg/l, and COD and BOD5 effluent of 50 mg/l and 38 mg/l. The result of bioreactor design were as follows: reactor volume of 171 m3, the sludge production of 54.6 kg/d, the oxygen requirement of 96.1 kg/d, the power requirements for blower of 5.1 kW, and the reactor dimension of 4x7.125x6 m for depth, length and wide.Key words : leachate, activated sludge, kinetics parameter